RESPONSE OF COWPEA (vigna unguiculata (L.)Walp) GENOTYPES TO SOWING DATES AND INSECTICIDE SPRAY IN SOUTH EASTERN NIGERIA - I. E. Ezeaku; B. N. Mbah; K. P. Baiyeri (Journal of Animal and Plant Sciences, 2017)
Cowpea productivity is generally hampered by insect pest attacks. Integrating host plant resistance, insecticide treatment and adjusting sowing date have been advocated as effective means of tackling insect pest menace on cowpea. Nine improved cowpea genotypes along with a local check were subjected to different sowing dates and agro-chemical treatments with the aim of determining their levels of response especially when exposed to zero insecticide treatment. Treatments were laid out in split-plot design with three replications across two years and locations. Results showed that when insecticide was not applied, yield and yield components were significantly (P<0.001) higher in early than late season presumably due to escape of genotypes from pest attacks. Untreated plots in late season resulted in zero grain yield for most genotypes. The genotype IT98K-131-2 was tolerant to the prevailing insect pests as it produced high grain yield of 770.5 kg ha-1 without chemical treatment across early and late season sowing. Grain yield of the rest of the genotypes were inconsistent across spray regimes, seasons and locations. The genotype IT97K-556-4 was the most responsive genotype to agro-chemical treatment producing significantly (P<0.001) higher grain yield when sprayed with insecticide and the least grain under zero spray. The genotype IT93K-452-1 gave significantly (P<0.001) higher 100 seed weight with or without insecticide treatment during both seasons and locations. Insecticide treatment significantly increased days to maturity and pod filling in late season at both locations while it significantly reduced days to flowering in Ishiagu location suggesting that agro-chemical treatment promoted grain yield in cowpea through delayed maturity and prolonged pod filling duration.
Keywords: Cowpea; sowing date; insecticide spray; host-plant resistance; southern eastern Nigeria